Higher Education and Artificial Intelligence: euphoria and Alarmism - A. I. Rakitov (Высшее образование в России)
Developed and developing countries have already entered the period which is commonly referred to as “knowledge society” or “information society”. In fact, these are the synonyms, because they point two linked circumstances. The first one is that modern science, technological and socio-political knowledge influence on all aspects of everyday life. The second is that in creation and production of all the knowledge the role of AI increases. Software and hardware of universal human intellect and artificial superintellect are being created with highest intensity. There creators dream that their systems can solve tasks on the level of human intellect. That is why the use of such systems in higher education has numerous evident advantages because makes it accessible, universal, capable of transmitting modern scientific knowledge into educational process. Through training of specialists higher education can influence on all the fields of social life. But many researchers see the negative effects of AI systems implementation too, and the most dangerous among them is the replacement of human intellect by artificial. In the extreme case this poses the serious danger for the whole mankind. That is why the accelerative appliance of AI demands further careful investigations. Neither euphoria nor alarmism are admissible in this sphere, especially when it concerns decision-making in educational policy. The implementation of AI systems in higher education requires a particular degree of discretion and precaution.